Time Management and Procrastination Patterns Among Undergraduate Agriculture Students - G. Malavika ,; Fathimath Shamsa ,; Akhil T. Allan,; S. Thara ,; Safna Vatakke Kandy Meethal,; S. Sownthariya ,; Allan Thomas, (Indian Journal of Extension Education, 2025)
Academic and personal success among students is achieved when they are able to manage their time effectively without procrastination.  The present study was conducted in 2025 to examine time management behaviors and procrastination tendencies among 101 undergraduate students across three batches—2021 (N=28), 2022 (N=33), and 2023 (N=40)—from the College of Agriculture, Vellayani. A 20-item standardized questionnaire, rated on a 5-point Likert scale, revealed a gradual decline in batch-wise mean scores: 2.238 (2021), 2.199 (2022), and 2.014 (2023). Students consistently scored highest in task prioritization (Mean = 3.17) and personal time management, while daily task listing (Mean = 1.48) and short task scheduling (Mean = 1.11) were persistent weaknesses. Heatmap and Spearman correlation analyses indicated behavioral consistency between the 2022 and 2023 cohorts (ρ = 0.818), and divergence with the 2021 batch. The results of the one-way ANOVA and paired t-tests indicate that there are no statistically significant differences in time management scores among the batches. The results emphasize the need for targeted interventions focused on micro-level planning to enhance academic self-regulation in early undergraduate years.